Outcomes of intrauterine device insertions by nurses in healthcare institutions: an integrative review - Liliane Ecco Canuto; Jonas Felisbino; Elizimara Ferreira Siqueira; Adriana Dutra Tholl; Nádia Chiodelli Salum; Lucia Nazareth Amante (Universidade Federal do Ceará, 2024)
Objective: to identify the outcomes of intrauterine device insertions by nurses in healthcare institutions. Methods: integrative review carried out in eight databases, with the help of a bibliographic reference manager, using the JBI model for analyzing the evidence level. The data was organized, categorized and discussed using descriptive summaries. Results: 10 studies made up the final sample, two with nurses only and the others with nurses and physicians. The main outcomes assessed were perforation and expulsion, with no significant differences between the professionals who performed the procedure. Success rates, continuity and satisfaction were similar between physicians and nurses. Conclusion: the outcomes of intrauterine device insertions by nurses in health institutions are similar to those carried out by physicians, with increased access, without increasing the complications related to this contraceptive method, contributing to comprehensive care in the field of reproductive planning. Contributions to practice: the findings could help nurses to tackle barriers and serve as a basis for guidelines and health policies that encourage the insertion of the intrauterine device by these professionals, especially in contexts where this practice does not yet take place.